Die landwirtschaftliche Aussiedlung in der strukturverbesserten Agrarlandschaft am Beispiel des Kreises Schleiden - Gallusser, Werner A. (ERDKUNDE, 1964)
The author investigates the problem of relocation of farmsteads (“Aussiedlung) carried out to help improve the structure of German agrarian regions. The area of investigation, the district of Schleiden in the northwest of the Eifel, is economically underdeveloped and in urgent need of having its agrarian structure improved. The farmsteads of the larger holdings have been transferred from the small clustered villages of this region, which, owing to the custom of divided inheritance (“Realteilung), is characterised by a high degree of fragmentation of farm land. The transfer has had a good and lasting effect not only on the individual farmsteads themselves but on the structure of the villages as well. In the whole region of the Eifel it is the transferred farms of Schleiden that have gained the maximum benefit from the purposeful activities of the authorities whose task consists of reallocation of scattered farmplots (“Flurbereinigung). These modern farmsteads have been organized on principles of ease of management and consist in most cases of a comfortable dwelling house, built as a bungalow, and of outhouses that are capable of further enlargement. They constitute a characteristic element in Schleiden, an agrarian region that has been transformed and brought up to date.